2008
DOI: 10.1007/s10800-008-9689-x
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity modification of proton conducting polymer gel electrolytes containing a weak acid (ortho-hydroxy benzoic acid) with the addition of PMMA and fumed silica

Abstract: Polymer gel electrolytes synthesized by dispersing nano size fumed silica in polymer gel electrolytes containing polymethylmethacrylate (PMMA), orthohydroxy benzoic acid (o-OHBA) and dimethylacetamide (DMA) have been studied by complex impedance spectroscopy, viscosity and pH measurements. The addition of acid, polymer and fumed silica has been found to result in an increase in conductivity and viscosity of gel electrolytes and gels with conductivity higher than the corresponding liquid electrolytes have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Similar results were obtained in [28] for gel electrolyte based on (methyl methacrylatemaleic anhydride) copolymer (P(MMA-MAh) with poly(ethylene glycol) monomethyl ether (PEGME) of different molecular weights, as well as for PMMA gels doped with H 3 PO 4 solutions in DMF [23]. At the same time for gel electrolyte based on PMMA and doped with o-hydroxybenzoic acid solution in dimethylacetamide [5] the contrary results were performed. It was shown that with PMMA molecular weight enhancement from 15,000 to 996,000 the conductivity lowering occurred.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Similar results were obtained in [28] for gel electrolyte based on (methyl methacrylatemaleic anhydride) copolymer (P(MMA-MAh) with poly(ethylene glycol) monomethyl ether (PEGME) of different molecular weights, as well as for PMMA gels doped with H 3 PO 4 solutions in DMF [23]. At the same time for gel electrolyte based on PMMA and doped with o-hydroxybenzoic acid solution in dimethylacetamide [5] the contrary results were performed. It was shown that with PMMA molecular weight enhancement from 15,000 to 996,000 the conductivity lowering occurred.…”
Section: Resultssupporting
confidence: 74%
“…Variety of polymer materials results in a wide range of polymeric matrix components for gel electrolytes synthesis. Various materials such as poly(vinylidene fluoride ) (PVdF) [1][2][3], poly(methyl methacrylate) (PMMA) [3][4][5][6], poly(ethylene glycol) (PEG) [7][8][9], poly(ethylene oxide) (PEO) [3,10,11], poly(glycidyl methacrylate) (PGMA) [12,13] poly(1-vinil-1,2,4-triazole) [14] and others are used as polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of investigations of PGEs based on poly(methyl methacrylate) (PMMA) or other available polymers doped with solutions of mineral and organic acids in aprotic solvents have been represented in a number of works . To increase the conductivity of gel electrolytes, strong acids, such as sulfuric or hydrochloric acid, can be used as a proton donor .…”
Section: Introductionmentioning
confidence: 99%
“…A literature review showed that the PGE conductivity can increase or decrease steadily or pass the maximum; this depends on the nature of both the acid and polymer and on their concentrations.…”
Section: Introductionmentioning
confidence: 99%